THE INFLUENCE OF AUTONOMOUS DIVING ON SENSES AND MENTAL PROCESSES - Dragan Krivokapić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
Diving is classified within a group of sports accompanied with an increased risk, yet it is a sport of full biological significance. Diving implies change of immediate human environment. Water, as the natural ambient for diving issues specific demands to the organism, which in turn influence decrease in psychophysical abilities when underwater, and in some instances, immediately after emerging from it. The most important factors influencing decrease in psychophysical abilities are: immersion, increased ambient pressure, characteristics of diving equipment and atmosphere separation. The senses and the mental processes of the diver are significantly altered during the autonomous diving. Loss of self-weight perception and pressure put on joints cause disorders in function of kinesthetic senses and vestibular apparatus, which in turn becomes reflected on proprioception. Coldness of water, especially at grater depths, induces decline in pain sensation as well as in aptness and mobility of fingers. Sight remains normal, but the image received is slightly changed due to refraction of light on boundary surfaces. Visual field is narrowed down to fit the limited diving mask field of view. At the same time, diffusion of light and color absorption brings about the loss of both ability to perceive things and contrasts when at depths .Objects tend to appear bigger and closer underwater. Hearing is changed owing to the fact that the sound is not carried through the air but through the water, yet the speed of transmission causes only slight difference of left and right ear stimulation. Mental processes, informationassessment, creation of clear mental images of the actual moment, abstract thinking, decision making, etc. are not effective and precise. This state can be partly ascribed to the above mentioned problems with senses, partly to the greater influence of emotional as opposed to rational, but also to the narcotic effect of nitrogen that is produced while diving with the compressed air diving apparatus at a certain depth, and which becomes more pronounced as the depth increases.